The Age of German idealism - Higgins, Kathleen Marie; Solomon, Robert C. (Routledge, 1993)
German Idealism was one of the most fertile and important movements in the history of Western philosophy. This volume includes eleven chapters on all aspects and the period's most influential philosophers, including Kant and Hegel.
Keywords: Idealism -- History -- 18th century.; Idealism -- History -- 19th century.; Philosophy, German -- 18th century.; Philosophy, German -- 19th century.; Idéalisme -- Histoire -- 18e siècle.; Idéalisme -- Histoire -- 19e siècle.; Philosophie allemande -- 18e siècle.; Philosophie allemande -- 19e siècle.; PHILOSOPHY -- Movements -- Idealism.; PHILOSOPHY / History & Surveys / General; PHILOSOPHY / General; Idealism; Philosophy, German; 1700-1899; Electronic books.; History